Strait Gate: Special Issue on Advances in Silicon Chemistry - Mitsuo Kira (Molecules, 2017)
Manufacturing high-purity element silicon and organic polysilicones are two major silicon industries, supporting the basis of the modern electronic industry and our daily lives [...]